Association of cardiac troponin I level with in-hospital and late mortality in dialysis patients - Shahram Taheri; Golbarg Ghomi; Alireza Nematollahi; Sayed Mohsen Hosseini (Journal of Research in Medical Sciences)
Background: Cardiovascular diseases (CVDs) are highly prevalent among the end-stage renal disease (ESRD) patients. Prognostic value of cardiac troponin I (cTnI) in patients with asymptomatic ESRD is less conclusive. This study was an observational study to evaluate correlation of first admitted cTnI level with early and late (during 6 months) hospitalization and mortality of ESRD patient admitted due to non-acute coronary and non-heart failure causes in ESRD patients. Materials and Methods: In this prospective observational study, 460 dialysis patients without overt CVD who were admitted at two university hospital were included and followed during 6 months. Patients’ demographic information and laboratory investigations including cTnI level and cause of admission were recorded. The association between cTnI level with in-hospital and late mortality was evaluated. Results: cTnI level was higher in female (35.9%), hemodialysis patients (28.1%), and patients with permanent catheter vascular access (29.4%). There were significant differences in level of triglyceride (TG), low-density lipoprotein (LDL) cholesterol, and high-density lipoprotein (HDL) cholesterol between patients with normal and abnormal cTnI levels (P < 0.05). Patients with abnormal cTnI levels had higher level of TG and LDL cholesterol and lower level of HDL cholesterol. cTnI levels were associated with higher in-hospital and 6-month follow-up mortality rate. In logistic regression analysis, only female gender (odds ratio [OR] =1.89, confidence interval [CI] =1.22–3.076) and TG (OR = 1.007, CI = 1.003–1.01) were positively and HDL cholesterol level (OR = 0.994, CI = 0.98–0.99) was negatively associated with increased cTnI level. cTnI level was associated with early (OR = 4.81, CI = 1.64–14.89) and late (OR = 4.31, CI = 1.61–10.96) mortality. Conclusion: Although in this study, cTnI level is not directly associated with cardiovascular disorders and admission and readmission causes, it is a strong predictor of early and late mortality.